Correlation of Basic Medical Laboratory Activities Performance with Grade Point Average of First-year Medical Students: Insights from New Medical School in Bekasi - Ridwansyah, Ridwansyah; Pariury, Phenny; Sopiyan, Riyan; Munawaroh, Siti (Faculty of Medicine Universitas Sebelas Maret, 2024)
Introduction: The surge in medical schools in Indonesia necessitates continuous quality improvement, particularly in curriculum and assessment. This study examines the correlation between first-year medical students' performance in basic medical science laboratory activities and their Grade Point Average (GPA).Methods: A retrospective observational study was conducted using secondary data from a new Medical School in Bekasi, Indonesia. student performance was reflected through the average final laboratory scores in the first year, while the GPA encompasses both medical and non-medical courses, totaling 21 credit hours. Data were collected from the university's information system database. Pearson's correlation test was used for normally distributed data, while Spearman's test was applied for non-normally distributed data.Results: The study included 27 first-year medical students with complete laboratory activity scores and GPA from the first two semesters. Significant positive correlations were found between laboratory performance in all subjects and GPA: Anatomy (R = 0.789, p < 0.0001), Histology (R = 0.7810, p < 0.0001), Microbiology (R = 0.6781, p = 0.0001), and Anatomical Pathology (R = 0.7024, p < 0.0001). These results highlight a strong correlation between laboratory performance and GPA in new medical school in Bekasi.Conclusion: This study emphasizes the importance of laboratory-based experiential learning in enhancing academic achievement among first-year medical students. Despite some limitations of this study, future research should explore the additional factors and include more medical schools to better understand the impact of laboratory performance on academic success.